Societal cost of day-care approach (DCA): A low-cost approach in urban and rural settings for management of childhood severe pneumonia in Bangladesh - Marufa Sultana; Jennifer Watts; Nur H. Alam; Nausad Ali; Abu S. G. Faruque; Sabiha Nasrin; Mohammod Jobayer Chisti; George J. Fuchs; Niklaus Gyr; Tahmeed Ahmed; Julie Abimanyi-Ochom; Lisa Gold (PLoS ONE, 2025)
Objective Childhood severe pneumonia is the leading cause of under-five deaths in Bangladesh. A new day-care management approach (DCA) was implemented in primary-level healthcare facilities in urban and rural areas of Bangladesh. Reliable cost estimates are important to determine the economic viability of the new management approach. The objective of this study were to estimate the mean societal cost per patient for a new Day-care approach (DCA) in managing childhood severe pneumonia, to assess cost variation in urban and rural healthcare settings, and to determine important cost predictors. Study design This study was conducted alongside a cluster randomized trial conducted in Bangladesh Children diagnosed with severe pneumonia were enrolled between November 2015 and March 2019. Employing a bottom-up micro-costing approach from a societal perspective, detailed household and provider cost data were collected from sixteen intervention facilities (n = 16). Data collection involved structured questionnaires administered face-to-face with facility staff, interviews with parents/caregivers, and patient record reviews. Analysis measured mean cost and cost variation across socio-economic groups, facility location, clinical variables, and determined cost-sensitive parameters. A p-value of < 0.05 was considered as statistically significant level. Results 1,745 children were enrolled, 63% were male, and 57% were less than a year old. The mean societal cost per patient was US$94.2 (95% CI: US$92.2, US$96.3) with a mean length-of-stay (LoS) of 4.1 days (SD ± 3.0). Costs of medical personnel (US$32.6), caregiver’s productivity loss (US$26) and medicines (US$22) were the major cost contributors. Mean cost was significantly higher for urban-located facilities compared to rural (difference US$17, 95% CI: US$12.6, US$20.8). No cost variation was found by age, sex, and clinical variables. Conclusion Findings suggest that this novel DCA management approach is a low-cost management option, and particularly beneficial for rural residences and therefore has the potential to reduce the overall cost burden for childhood severe pneumonia management. These findings have implications for policy-making decisions in resource-poor settings for childhood pneumonia management.